Microquimerismo fetal em pacientes com lupus eritematoso sistêmico: uma contribuição para o estudo da fisiopatologia das doenças auto-imunes - Abbud Filho, Mario (2006)
Systemic lupus erythematosus (LES) is a serious systemic autoimmune disease of which the pathogenesis remains elusive. Bi-directional cell traffic during pregnancy gives rise to fetal microchimerism (FMC). There is accumulating evidence suggesting that FMC can cause or exacerbate autoimmunity. Objetive. To determine the incidence of FMC in LES patients (pts) and to assess the effect of pregnancy and some epidemiological characteristics of LES on the FMC. Patientes and Methods. Real time polymerase chain reaction for specific Y chromosome sequences was used to detect fetal male cells (IPF) in the peripheral blood of 46 women selected according to this criteria: 1- pregnancy of at least one male offspring; 2- absence of history of previous transfusions, miscarriages or transplants. Information was obtained on the age of the mother at first male birth, number of male offspring, time since birth of the first son (time of microchimerism), time since disease diagnosis and renal involvement of LES.Results.Twenty eight pts and 18 healthy women were included in the study. The number of fmc/ml of maternal blood was higher among LES pts than in control group (252 ± 654 vs 2,13 ± 3,7 fmc/ml; p= 0,029). Multiple linear regression did show a strong positive correlation between the number of fmc/ml and the length of the disease (p= 0,027). The number of male cells also increase with duration of microchimerism in LES pts ( 15y = 140 ± 382; >15y = 395 ± 860 fmc/ml; p= 0,003) while slightly decreasing among healthy women during the same time periods (2,55 ± 4,34; 2,66 ± 3,79; 1,64 ± 3,81fmc/ml; p= NS). FMC was not associated with this number of male births and was also not associated with the mother s age at the birth of the first son. Higher numbers of fmc/ml were detected among pts without nephropathy when compared to those of pts with lupus nephritis (388 ± 827 YV 95,5 ± 338 fmc/ml; xiii p=0,019). This same observation was made in pts 18 years old at first male birth 9=(355 ± 623 YV 0,23 ± 0,22 fmc/ml respectively; p= 0,028). Conclusions. Our data demonstrates that the number of fmc/ml is higher in LES pts than in healthy women and it does increase with length of disease and duration of microchimerism. These results strongly suggest that in LES pts fetal microchimeric cells do proliferate with time but decrease or tend to disappear in healthy women. It is possible that FMC may not be totally detrimental to the host because it may provide some benefits in lupus nephritis cases.